(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is a technological marvel of the modern world, and it has already revolutionized the way in which people think, interact, gather and process information, do research, earn a living, educate and entertain themselves. Human institutions are going to change their style of operation and established new relationships with citizens nationally and internationally. It is suggested that about 60 million people used the Net in 1995, the number of users increased to 200 million at the beginning of 2000 and internet users by a billion people all over the world in 2005. This is one sixth of the total population on earth. This may be a highly optimistic estimate. Actually the internet links subscribes are globally through the world wide web. Every subscribers can be reached within minutes, if not seconds. It is a supercomputer network. However, there is no doubt that the number of Nets users in increasing fast. Therefore, in this paper we have tried to explore the impact of internet in terms of its positive as well as negative on the users. Further, media often report that intense use of the internet increases the risk of isolation, alienation, and withdrawal from society. Illegal or inappropriate material can be found in the internet and also it can be used for spreading computer viruses. But available evidence shows that internet actually increases sociability, civil engagement, interchange ideas and materials among universitycollege professors and students and the intensity of family and friends relationship, in all culture.